Is Breast Self Examination (BSE) still relevant? a study on BSE performance among female staff of University of Malaya - Dahlui, M.; Ng, C.W.; Al Sadat, N.; Ismail, S.; Bulgiba, A.M. (2011)
Objectives: This study aimed to determine the rate of breast self examination (BSE) among the female staff of University of Malaya and to determine the role of BSE in detecting breast abnormalities. Methods: A total of 1598 questionnaires were posted to all female staff, aged 35 years and above. Their knowledge on breast cancer, practice of BSE and detection rate of breast abnormality as confirmed by CBE was determined. Results: The response rate for this study was 45 percent (714 respondents). The rate of respondents having awareness on breast cancer was 98.7 percent. Eighty four percent (598) of the respondents had performed BSE in their lifetime. However, in only 41 was it regular at the recommended time. Forty seven percent (334) had undergone CBE at least once in a lifetime but only 26 (185) had CBE at least once in the past 3 years, while 23 (165) had had a mammogram. There was a significant relationship between CBE and BSE whereby those who had CBE were twice more likely to do BSE. Nineteen percent (84 respondents) of those who did BSE claimed they had detected a breast lump. Of these, 87 (73) had gone for CBE and all were confirmed as such. Conclusion: BSE is still relevant as a screening tool of breast cancer since those who detect breast lump by BSE will most probably go for further check up. CBE should be done to all women, especially those at highest risk of breast cancer, to encourage and train for BSE.